Biomass and phosphorus content in giant bamboo cuttings influenced by phosphate fertilization - Dunaiski, Felipe Antico; Pauletti, Volnei; Motta, Antônio Carlos Vargas; Gotz, Lenir Fátima (Scientia Agraria Paranaensis, 2019)
Dendrocalamus asper, known as giant bamboo or bamboo-bucket, has been used as a substitute for wood and fiber, due mainly to its wide availability, rapid growth rate, short cycle and traditional use as construction material. In general, its cultivation is carried out on phosphorus-deficient soils, using vegetative propagation, mainly from cuttings. Thus, the aim of this study was to evaluate the effect of fertilization with phosphorus doses on the biomass allocation in roots, leaves and stems and on the level and content of P in leaves and roots of bamboo cuttings. The experiment was conducted in a greenhouse, using soil with low P content (2.4 mg dm-3). The treatments consisted of six doses of phosphorus (0, 20, 40, 80, 160 e 320 kg ha-1 of P2O5). The experimental design was a randomized block design, with five replications. After 90 days, the seedlings were collected and evaluated the following variables: dry mass of roots, leaves, stems and total dry mass, level and P content in leaves and roots. Phosphate fertilization promoted greater development of the cuttings and resulted in higher content of P. In general, the species D. asper responds positively to phosphate fertilization.